Ion gel-doped perovskite film and photoelectric device

By introducing 0.01%-10% ionic gel into perovskite films, adjusting its mechanical properties and achieving self-repair at room temperature, the shortcomings of flexible perovskite batteries in bending resistance and mechanical stability are solved, and the company has significantly improved the Its efficiency and mechanical stability are achieved.

CN115020591BActive Publication Date: 2025-01-14JILIN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210676200.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-15
Publication Date
2025-01-14
Estimated Expiration
2042-06-15

AI Technical Summary

Technical Problem

Flexible perovskite batteries have shortcomings in terms of efficiency and mechanical stability, especially in terms of poor bending resistance and high voltage loss. The fracture ratio of existing polymer materials is small and cannot be self-repaired at room temperature, and the doping amount is Limit carrier transmission.

Method used

Using ionic gel with a mass fraction of 0.01%-10% as an additive, by adjusting the solubility of the polymer segment in the ionic liquid and the ratio of the ionic liquid to the polymer, an ionic conductive material with high toughness and elongation is formed for calcium. Preparation of titanium ore films enhances grain boundary fracture energy and achieves self-healing at room temperature.

Benefits of technology

It significantly improves the mechanical stability and efficiency of perovskite films, avoids grain boundary cracks and interlayer peeling during bending, enhances the mechanical stability of perovskite devices, and uses the self-healing characteristics of ionic gels to Repairing grain boundaries under extreme stresses improves the performance of optoelectronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115020591B_ABST
    Figure CN115020591B_ABST
Patent Text Reader

Abstract

The present invention discloses a perovskite film and a photoelectric device doped with an ion gel, and belongs to the field of perovskite photoelectric devices. The technical problem to be solved by the present invention is to overcome the problem that the existing perovskite is susceptible to stress damage and the flexible device has poor anti-bending ability, and seek a more effective additive that can simultaneously improve the efficiency and mechanical stability of the perovskite battery. In the present invention, the ion gel is introduced into the perovskite film, which will significantly improve the fracture energy of the grain boundary and passivate defects. The ion gel is composed of a high molecular organic polymer and an ionic liquid, wherein the mass fraction of the ionic liquid is 30%-80%, and the monomer of the high molecular organic polymer includes a monomer A of a rigid polymer and a monomer B of a flexible polymer, and the mass ratio A:B is (1:10) to (1:2); in addition, the regulation of mechanical properties by ionic liquids and polymer functional groups can be combined with the passivation of perovskite grain boundaries and surfaces, so as to simultaneously improve the photoelectric conversion efficiency and mechanical stability of perovskite photoelectric devices, especially flexible devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of perovskite photoelectric devices, and specifically relates to the application of ion gel as an additive in constructing a high-efficiency, bend-resistant, flexible perovskite battery. Background Art

[0002] The compatibility of flexible devices is an outstanding advantage of perovskite solar cells. So far, flexible perovskite cells have made great breakthroughs in efficiency and stability. However, compared with the efficiency of more than 25% and ultra-low voltage loss of rigid devices, the reduced fill factor and increased voltage loss of flexible devices greatly limit their efficiency to be comparable to that of rigid devices. On the one hand, this is because the additional recombination process introduced by its more intrinsic defects increases the voltage loss and reduces the parallel resistance, resulting in a decrease in voltage and fill factor. On the other hand, flexible devices are inevitably subjected to greater external mechanical stress during processing and operation, especially for devices prepared using the R2R process. The resulting microcracks or interlayer peeling may produce new defect sites.

[0003] Existing technologies have made phased progress by adding polymer materials with adhesive, buffering, and self-healing properties at grain boundaries or interfaces. However, the fracture ratio of these materials is usually small, and the broken chemical bonds after exceeding the elastic limit cannot be repaired or require additional energy input to repair. In addition, due to the poor conductivity of doped polymers, excessive doping will limit the effective transport of carriers, so the doping amount is generally on the order of 0.01%, which further reduces its stress buffering effect. In addition, the weak interaction between polymer chain links and perovskites and the single functional group make its ability to passivate defects weak. Therefore, we urgently need to develop new types of materials to improve the stability of traditional perovskite cells under stress conditions and improve the efficiency and mechanical stability of perovskite flexible cells. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the technical problem to be solved by the present invention is to overcome the poor bending resistance of existing perovskite flexible devices and to seek a more effective additive to simultaneously improve the efficiency and mechanical stability of perovskite flexible batteries.

[0005] Ion gel is a solid mixture with ionic conductivity, usually a mixture of high molecular organic polymers and salt electrolyte materials that can be electrolyzed into ions. Because its polymer molecular chains are interconnected or entangled to form a spatial network structure, the structural gaps are filled with anions and cations as dispersion media, which is similar to the structure of traditional gels, so it is called "ion gel". After a lot of research, the inventors found that ion gel, as an ion conductive material with high toughness and elongation, can adjust the mechanical properties of ion gel by adjusting the solubility of different polymer segments in ionic liquids and the ratio of ionic liquids to polymers, and can achieve rapid room temperature self-repair. If it is introduced into the grain boundaries of perovskites, it will significantly increase the fracture energy at the grain boundaries and prevent the generation of defects. In addition, the regulation of mechanical properties by ionic liquids and polymer functional groups can be combined with the passivation of perovskite grain boundaries and surfaces to simultaneously improve the efficiency and mechanical stability of perovskite flexible batteries.

[0006] To achieve the above objectives, the present invention adopts the following technical solutions:

[0007] The present invention provides an ion gel-doped perovskite film, wherein the perovskite film contains 0.01%-10% by mass of ion gel relative to the perovskite;

[0008] The ion gel is composed of a high molecular organic polymer and an ionic liquid, wherein the mass fraction of the ionic liquid is 30%-80%, and the monomers of the high molecular organic polymer include a monomer A of a rigid polymer and a monomer B of a flexible polymer, and the mass ratio A:B is (1:10) to (1:2);

[0009] The monomer A of the rigid polymer is acrylamide and its derivatives; the monomer B of the flexible polymer is acrylic acid or a derivative of acrylic acid ester;

[0010] The ionic liquid is an imidazole ionic liquid, the cation of which is 1-ethyl-3-methylimidazole or 1-butyl-3-methylimidazole; the anion of which is ethyl sulfate, bis(trifluoromethanesulfonyl)imide, tetrafluoroborate or hexafluorophosphate.

[0011] A method for preparing an ion gel-doped perovskite film is carried out by one or more of the following methods:

[0012] Method 1: adding and dissolving the ion gel in the perovskite precursor solution at 0.01%-10% relative to the solute mass of the perovskite precursor solution, coating the ion gel perovskite composite precursor mixed solution on the substrate, and annealing at 50-150° C. for 1-90 minutes to form an ion gel-doped perovskite film;

[0013] Method 2: First, apply a solution of ion gel with a concentration of 0.02-100 mg / mL on the substrate, and anneal at a temperature of 50-150°C for 10-60 minutes to form an ion gel film. Then, apply a perovskite precursor solution on the ion gel film, and anneal at 50-150°C for 1-90 minutes to form an ion gel-doped perovskite film.

[0014] Method 3: Coat 0.02-100 mg / mL of ion gel solution on the prepared perovskite film, and anneal at 50-150° C. for 1-90 minutes to form an ion gel-doped perovskite film.

[0015] The coating is carried out by conventional processes in the art, such as spin coating, spray coating, blade coating, brush printing, screen printing, micro-gap coating, air knife coating, slit extrusion coating, and a combination of one or more of inkjet printing and roll-to-roll printing, such as blade coating.

[0016] The substrate is a conventional conductive substrate in the art, such as a conductive glass substrate or a PET / ITO flexible transparent conductive substrate.

[0017] In the first method, the solvent of the perovskite precursor solution is one or more of N,N-dimethylformamide, methylamine acetate, methylamine, dimethyl sulfoxide, γ-butyrolactone, 2-methoxyethanol, and acetonitrile; the solute of the perovskite precursor solution is a perovskite component commonly used in the field and a conventionally doped and modified perovskite component, including but not limited to a perovskite material based on a mixed component of A, B and X, wherein A is a methylamine ion (MA + ), formamidinium ion (FA + ), dimethylamine ion, acetamidine ion, guanidine ion, one or more of cesium ion and rubidium ion, B is divalent lead ion (Pb 2+ ), divalent tin (Sn 2+ ) or other conventional metal ions or their mixture ions, X is one or more ions of chloride ion, bromide ion, and iodide ion; the concentration of the solute in the perovskite precursor solution is 0.3-2.5 mol / L commonly used in the art, preferably 1 mol / L or 1.2 mol / L.

[0018] The solvent of the ion gel solution in the second method is any solvent that can dissolve the ion gel, such as methanol, ethanol, trifluoroethanol, isopropanol, sec-butanol, N,N-dimethylformamide and dimethyl sulfoxide.

[0019] The solvent of the ion gel solution in the second method is any solvent that can dissolve the ion gel but not the underlying perovskite film, including trifluoroethanol and sec-butanol.

[0020] The preparation method of ion gel in ion gel-doped perovskite film comprises the following specific steps:

[0021] 1) Mixing a rigid A polymer monomer and a flexible B polymer monomer at a mass ratio of A:B of (1:10) to (1:2);

[0022] 2) adding ionic liquid into the mixed polymer monomers at a mass fraction of 30%-80%, and stirring thoroughly until it is completely dissolved into a clear solution;

[0023] 3) Add photoinitiator and stir to dissolve;

[0024] 4) Irradiate with ultraviolet light for 10 minutes to 5 hours to initiate a free radical polymerization reaction, causing the solution to polymerize into an ion gel.

[0025] Between step 2) and step 3), a step of adding a cross-linking agent and fully stirring is also included; the cross-linking agent is methylene bisacrylamide.

[0026] The initiator includes but is not limited to photoinitiator 2959, photoinitiator 1173 and other initiators suitable for free radical polymerization.

[0027] The ion gel-doped perovskite film is used to prepare perovskite photoelectric devices, which include but are not limited to solar cells, electroluminescent devices, high-energy ray detectors, light detectors, etc., especially corresponding flexible devices.

[0028] The photoelectric device comprises all or part of the following structures: substrate / transparent electrode / hole transport layer / active layer / electron transport layer / barrier layer / electrode layer or substrate / transparent electrode / electron transport layer / active layer / hole transport layer / interface layer / electrode layer, and the active layer is a perovskite film doped with ion gel;

[0029] The transport layers on both sides of the active layer are made of conventional hole transport materials and electron transport materials in the art; the hole transport material is poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], PEDOT:PSS or carbazole hole transport material; the electron transport material is C 60 , C 70 , C 60 Derivatives, C 70 derivatives, TiOx, SnO2 or ZnO;

[0030] The electrode on the outside of the transmission layer is a transparent electrode or an opaque electrode commonly used in the art, such as a transparent conductive polymer polyethylene dioxythiophene: sodium polyvinyl benzene sulfonate (PEDOT: PSS) electrode, an ITO transparent electrode, and an opaque electrode such as a carbon electrode, a graphene electrode, a carbon nanotube electrode, a metal grid electrode, a nano-metal wire film, and a metal film.

[0031] The substrate below the electrode is a conventional rigid or flexible substrate in the art, such as glass, metal plate, metal-clad plate, silicon wafer, polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyurethane (PU), polydimethylsiloxane (PDMS).

[0032] The barrier layer is a conventional interface material in the field of perovskite cells, such as BCP.

[0033] The packaging layer on the outside of the device is a conventional packaging material in the art, such as hot melt adhesive film, UV curing adhesive film, epoxy resin, and two-component adhesive (AB adhesive).

[0034] The positive and progressive effects of the present invention are:

[0035] (1) Compared with the traditional perovskite film, the ion gel-perovskite composite film prepared by the present invention greatly enhances the toughness of the perovskite grain boundary, so that the stress of the perovskite film during bending can be buffered and dissipated by the stretching of the ion gel, thus avoiding grain boundary cracks and interlayer delamination, and enhancing the mechanical stability of the perovskite device.

[0036] (2) Unlike traditional buffer materials at grain boundaries, which usually have relatively small fractures and cannot be repaired or require additional energy input after exceeding the elastic limit, the unique room-temperature self-healing properties of ion gels allow the grain boundaries of perovskite films to be significantly repaired after stress release, even if cracks occur under extreme stress, further enhancing the mechanical stability of perovskite devices.

[0037] (3) As an open and adjustable polymer network, the ion gel introduces abundant passivation sites into the ionic liquid and polymer functional groups, which reduces the defect concentration of the perovskite film. This significantly improves the performance of optoelectronic devices based on the ion gel-perovskite composite film.

[0038] (4) The ion gel-doped precursor solution has better spreadability on the hydrophobic substrate, which is conducive to the preparation of high-quality perovskite films and optoelectronic devices on the hydrophobic surface.

[0039] In summary, ion gel as an additive can simultaneously improve the efficiency and mechanical stability of optoelectronic devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 These are digital photos of the ion gel synthesized in Example 1 before and after stretching.

[0041] Figure 2 This is the load-elongation curve of the ion gel in Example 1.

[0042] Figure 3The resistance-time curve of the ion gel prepared in Example 1 before and after self-repair.

[0043] Figure 4 The microscopic morphology of the ion gel-perovskite composite film prepared in Example 2.

[0044] Figure 5 Comparison of the X-ray photoelectron spectroscopy carbon spectra (left) and sulfur spectra (right) of the ion gel-perovskite composite film and ion gel film prepared in Example 2 and Example 1.

[0045] Figure 6 Comparison of JV curves of the perovskite solar cells prepared in Example 3 and Comparative Example 1.

[0046] Figure 7 Comparison of the bending characteristics of the perovskite solar cells prepared in Example 3 and Comparative Example 1 when the bending radius is 5 mm.

[0047] Figure 8 The figure compares the bending characteristics of the perovskite solar cells prepared in Example 3 and Comparative Example 1 when the bending radius is 2.5 mm, as well as the room temperature self-repair effect of the device in Example 3.

[0048] Fig. 9 Comparison of JV curves of the perovskite solar cells prepared in Example 4 and Comparative Example 1.

[0049] Fig.10 Comparison of the spreadability of perovskite precursor solution doped or not doped with ion gel on polytetrafluoroethylene substrate. DETAILED DESCRIPTION

[0050] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0051] Example 1

[0052] 1. Weigh 69 mg of acrylamide and mix with 100 μL of 2,2,2-trifluoroethyl acrylate.

[0053] 2. Add 270 μL of 1-ethyl-3-methylimidazolium ethyl sulfate ionic liquid to the mixed polymer monomers and stir thoroughly until it is completely dissolved into a clear solution.

[0054] 3. Add 0.2 mg of photoinitiator 2959 to the solution and stir to dissolve.

[0055] After the air in the solution was exhausted and inert gas was introduced, the solution was exposed to ultraviolet light with a wavelength of 365 nm for 10 minutes to polymerize the solution into an ion gel.

[0056] Example 2

[0057] 0.7 mg of the ion gel in Example 1 was added to 1 mL of 1.1 mol / mL MAPbI3 N,N-dimethylformamide precursor solution, and the solvent was fully stirred. The ion gel-perovskite composite precursor solution was coated on the PET-ITO substrate by a doctor blade method with a doctor blade slit of 55 μm. The solution was annealed at 100°C for 10 minutes to form an ion gel-perovskite composite film.

[0058] Example 3

[0059] After the cleaned PET-ITO substrate was treated with UV ozone for 15 minutes, a 2 mg / mL PTAA toluene solution was coated on it. After annealing at 100 degrees for 10 minutes, the ion gel-perovskite composite precursor solution in Example 2 was coated by a doctor blade method with a slit of 55 μm. The substrate was annealed at 100 degrees for 10 minutes to form an ion gel-perovskite composite film. A 20 nm thick C 60 , 7.5nm thick BCP, 80nm thick Cu electrode to make ion gel doped flexible perovskite battery device.

[0060] Example 4

[0061] The anion of the ionic liquid in Example 1 was replaced with an equimolar amount of bis(trifluoromethanesulfonyl)imide, and other operations remained unchanged. The obtained ion gel was prepared into an ion gel-doped flexible perovskite battery device according to the methods of Examples 2 and 3.

[0062] Comparative Example 1

[0063] The ion gel-perovskite composite precursor solution in Example 3 was replaced with an N,N-dimethylformamide precursor solution of common MAPbI3 with the same concentration. The rest of the operations were the same as in Example 3, and a reference device was obtained.

[0064] Effect Example 1

[0065] Take the ion gel synthesized in Example 1 and record the length before and after stretching. Figure 1 As shown, it shows that the elongation at break of the ion gel is greater than 1200%. The load-elongation curve is further characterized by a universal testing machine. Figure 2 As shown, it has a large fracture energy. We further cut open part of the ion gel with a knife and used a digital source meter to observe the change of its resistance over time. Figure 3 It is shown that it has good self-repairing ability.

[0066] Effect Example 2

[0067] The ion gel-perovskite composite film prepared in Example 2 was taken and its morphology was observed using a scanning electron microscope. Figure 4 As shown in the figure, it can be clearly seen that as the distance between grains increases, the ion gel at the grain boundary is gradually stretched, but not disconnected. The X-ray photoelectron spectra characterizing the ion gel-perovskite composite film and the ion gel film are shown in Figure 5 As shown. The results show that the C peak in the carbonyl group of the amide functional group of the ion gel and the S peak in the ionic liquid 1-ethyl-3-methylimidazolium ethyl sulfate both shifted significantly, indicating that there is a strong interaction between the ion gel and the perovskite.

[0068] Effect Example 3

[0069] The perovskite solar cells prepared in Example 3 and Comparative Example 1 were tested for JV curves and performance parameters. Figure 6 The results show that the interaction between the ion gel and the perovskite has a good passivation effect on defects, so that the filling factor and voltage of the device in Example 3 are significantly enhanced compared with the device in Comparative Example 1. Further bending stability tests are shown in Figure 7 As shown, it can be seen that after 5000 convex bends with a bending radius of 5mm, the device performance of the device in comparative example 1 retained less than 80%, while the device in embodiment 3 still retained an average efficiency of more than 90% after 25000 bends. When tested with a bending radius of 2.5mm, the average efficiency of the device in comparative example 1 was only about 20% of the initial value after 500 bends, while the device in embodiment 3 retained an average efficiency of more than 85% after 1000 bends, and after 10 hours of room temperature self-repair, the average efficiency returned to about 90% of the initial value.

[0070] Effect Example 4

[0071] Take the perovskite solar cell prepared in Example 4 and test the JV curve and its performance parameters as follows: Fig.10 The results show that the ion gels containing different ionic liquids can significantly enhance the fill factor and voltage of the device relative to the device in Comparative Example 1.

[0072] The rigid polymer monomer A may be acrylamide and its derivatives, and the flexible polymer monomer B may be acrylic acid or acrylate derivatives and other common polymer monomers in the plasma gel field. Theoretically, all of them can realize the technical solution of the present invention.

Claims

1. An ion gel-doped perovskite film, characterized in that: The perovskite film contains 0.01%-10% by mass of ion gel relative to the perovskite; The ion gel is composed of a high molecular organic polymer and an ionic liquid, wherein the mass fraction of the ionic liquid is 30%-80%, and the monomer of the high molecular organic polymer is selected from a monomer A of a rigid polymer and a monomer B of a flexible polymer, and the mass ratio A:B is (1:10) to (1:2); The monomer A of the rigid polymer is acrylamide and its derivatives; the monomer B of the flexible polymer is acrylic acid or a derivative of acrylic acid ester; The ionic liquid is an imidazole ionic liquid, the cation of which is 1-ethyl-3-methylimidazole or 1-butyl-3-methylimidazole; the anion of which is ethyl sulfate, bis(trifluoromethanesulfonyl)imide, tetrafluoroborate or hexafluorophosphate.

2. A method for preparing an ion gel-doped perovskite film as claimed in claim 1, characterized in that: The preparation method is carried out by any one or more combinations of methods 1 to 3: Method 1: Add and dissolve the ion gel in the perovskite precursor solution at 0.01%-10% relative to the mass of the perovskite, and apply the ion gel perovskite composite precursor mixed solution on the substrate, and anneal at 50-150°C for 1-90 minutes to form an ion gel-doped perovskite film; Method 2: First, a solution of ion gel with a concentration of 0.02-100 mg / mL is coated on the substrate, and annealed at a temperature of 50-150°C for 10-60 minutes to form an ion gel film; then, a perovskite precursor solution is coated on the ion gel film, and annealed at 50-150°C for 1-90 minutes to form an ion gel-doped perovskite film; Method 3: Coat 0.02-100 mg / mL of ion gel solution on the prepared perovskite film, and anneal at 50-150°C for 1-90 minutes to form an ion gel-doped perovskite film.

3. The method for preparing an ion gel-doped perovskite film according to claim 2, characterized in that: The coating is carried out by conventional processes in the art, selected from: spin coating, spray coating, blade coating, brush printing, screen printing, micro-gap coating, air knife coating and slit extrusion coating, or a combination of one or more of inkjet printing and roll-to-roll printing.

4. The method for preparing an ion gel-doped perovskite film according to claim 2, characterized in that: The substrate is a conventional conductive substrate selected from: a conductive glass substrate or a conductive polymer substrate.

5. The method for preparing an ion gel-doped perovskite film according to claim 2, characterized in that: In the first method, the solvent of the perovskite precursor solution is one or more of N,N-dimethylformamide, methylamine acetate, methylamine, dimethyl sulfoxide, γ-butyrolactone, 2-methoxyethanol, and acetonitrile; the solute of the perovskite precursor solution is a perovskite material based on a mixed component of A, B, and X, wherein A is a methylamine ion MA + , formamidinium ion FA + , dimethylamine ion, acetamidine ion, guanidine ion, cesium ion and rubidium ion, and B is a divalent lead ion Pb 2+ 、Divalent tin ion Sn 2+ or a mixture thereof, X is one or more ions selected from chloride ion, bromide ion and iodine ion; and the concentration of the solute in the perovskite precursor solution is 0.3-2.5 mol / L.

6. The method for preparing an ion gel-doped perovskite film according to claim 2, characterized in that: The solvent of the ion gel solution in the second method is any solvent that can dissolve the ion gel, selected from: methanol, ethanol, trifluoroethanol, isopropanol, sec-butanol, N,N-dimethylformamide and dimethyl sulfoxide; The solvent of the ion gel solution in the third method is any solvent that can dissolve the ion gel but not the underlying perovskite film, selected from: trifluoroethanol and sec-butanol.

7. The method for preparing an ion gel-doped perovskite film according to claim 2, characterized in that: The preparation method of ion gel in ion gel-doped perovskite film comprises the following specific steps: 1) Mixing a rigid A polymer monomer and a flexible B polymer monomer at a mass ratio of A:B of (1:10) to (1:2); 2) Add ionic liquid to the mixed polymer monomers at a mass fraction of 30%-80%, and stir thoroughly until it is completely dissolved into a clear solution; 3) Add photoinitiator and stir to dissolve; 4) irradiating with ultraviolet light for 10 minutes to 5 hours to initiate a free radical polymerization reaction, so that the solution is polymerized into an ion gel; the photoinitiator is an initiator suitable for free radical polymerization, selected from photoinitiator 2959 and photoinitiator 1173.

8. The method for preparing an ion gel-doped perovskite film according to claim 7, characterized in that: Between step 2) and step 3), a step of adding a cross-linking agent and fully stirring is also included; the cross-linking agent is methylene bisacrylamide.

9. The use of the ion gel-doped perovskite film according to claim 1 for preparing a perovskite photoelectric device, characterized in that: The perovskite photoelectric device is selected from: a solar cell, an electroluminescent device, a high-energy ray detector and a light detector.

10. The use of the ion gel-doped perovskite film according to claim 9 for preparing a perovskite photoelectric device, characterized in that: The photoelectric device comprises all or part of the following structures: substrate / electrode / hole transport layer / active layer / electron transport layer / barrier layer / electrode layer or substrate / electrode / electron transport layer / active layer / hole transport layer / interface layer / electrode layer, wherein the active layer is an ion gel-doped perovskite film; The transport layers on both sides of the active layer are made of conventional hole transport materials and electron transport materials in the art; the hole transport material is poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], PEDOT:PSS or carbazole hole transport materials; The electron transport material is C 60 , C 70 , C 60 Derivatives, C 70 derivatives, TiOx, SnO2 or ZnO; The electrode is a common transparent electrode or opaque electrode in the art, selected from: transparent conductive polymer polyethylene dioxythiophene: sodium polyethylene benzene sulfonate electrode or FTO or ITO transparent electrode, carbon electrode, graphene electrode, carbon nanotube electrode, metal grid electrode, nano metal wire film or metal film; The substrate is a conventional rigid or flexible substrate in the art, selected from: glass, metal plate, metal-clad plate, silicon wafer, polyethylene terephthalate, polyethylene naphthalate, polyurethane, polyimide or polydimethylsiloxane; The barrier layer is a conventional interface material in the field of perovskite cells, selected from: fullerene derivatives, BCP; The packaging layer on the outside of the device is a conventional packaging material in the art, selected from: hot melt adhesive film, UV curing adhesive film, epoxy resin or multi-component adhesive.

Citation Information

Patent Citations

  • Method for preparing flexible transparent conductive electrode

    CN104992778A

  • Preparation method for flexible and transparent composite ionic liquid gel conductive electrode

    CN105140408A